Maternal Self-Health on Toddler Diarrhea associated with Environmental Sanitation in Deli Tua Health Center Area - Ira Aini Dania; Adi Raja Brando Lubis; Surya Akbar; Dewi Pangestuti; Ramadhan Bestari (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Morbidity surveys conducted by the Sub-directorate of Disease Control Prevention and Environmental Health (P2PL) of the Health Office from 2000 to 2010, there was an increase in the incidence of diarrhea. Many factors contribute to the increasing incidence of diarrhea, especially among children under five years of age, including maternal personal hygiene and environmental sanitation. In 2014 there were six diarrhea outbreaks that were widely spread in five provinces and six districts or cities, the number of patients increased to 2,549 people with twenty-nine deaths (CFR 1.14%) and North Sumatra was one of the five provinces with the most cases. This study was conducted in Deli Tua Subdistrict, Deli Serdang Regency, North Sumatra, for approximately 8 months from April to December 2016 is an observational analytic study with a cross sectional approach. The sample of this study were 50 mothers who brought their toddlers to the Deli Tua Health Center. The statistical analysis used was chi square test. The results showed there was a relationship between the mother's hand washing behavior (p = 0.05), the use of water sources (p = 0.04) and the age of toddlers (p = 0.00) with the incidence of diarrhea in toddlers in the Deli Tua Health Center working area.